When less expected problems become critical: first-year teaching in early childhood classes. Issue 3 (27th May 2022) - Temiz, Zeynep; Haser, Çiğdem
ABSTRACT: The aim of this study was to explore preservice early childhood education (ECE) teachers' expectations and concerns before they started their careers and the challenges they faced in the first year. Sixteen preservice ECE teachers from the same teacher education programme in Turkey were interviewed about their expectations for their first year before their graduation. Then, they were interviewed at the end of the first and the second semesters about their experiences and difficulties of teaching in public schools, and the positive aspects of their work. Although participants were aware of many difficulties in public schools, some of the challenges they faced in disadvantaged school settings, such as infrastructural inadequacies, non-curricular tasks, and material shortages, were beyond their initial anticipation and not in line with their teacher education programme experiences. Teacher education programmes should provide pre-service teachers with experiences in disadvantaged school settings to be better prepared.